The Concept of the Epistemological Obstacle at Gaston Bachellar and its Essential Forms - Razok, Ibrahim; Naser, Alaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The importance of this research is that it is one of the rare researches that touch on the philosophy of science at the French philosopher Gaston Bachler, And the role played by this philosopher in the development of the science of epistemology through the epistemological concepts that he introduced to this science, Such as the concept of epistemological obstacle and the concept of epistemological estrangement in addition to the concept of temporal regression and the relationship of these concepts with each other, which contributed to the enrichment of the epistemology and its evolution.